Excessive apoptosis, glycolysis, and abnormal levels of gluconeogenase in rheumatoid arthritis involves in the dysregulation of glucose metabolism: an animal model study - Hui Pi; Qiang Fu; Juan Liu; Haotong Zhou; Youlian Wang (Autoimmunity)
Rheumatoid arthritis (RA) has been associated with an elevated risk of developing disorders related to glucose metabolism, including decreased insulin secretion, impaired glucose tolerance, and type 2 diabetes mellitus. The previse mechanisms underlying this association remain incompletely elucidated. In this study, we utilized a cohort of fifty Wistar female rats, establishing a type II collagen-induced arthritis (CIA) model (n = 30). Out observations indicated abnormal glucose and inulin levels in the CIA rats, accompanied by diminished β cell function. Additionally, we detected elevated cytokines levels and increased apoptosis within the pancreatic tissue of the CIA rats. It is hypothesized that the heightened apoptosis may be induced by cytokines, potentially leading to reduced insulin synthesis and dysregulated glucose metabolism. Through transcriptomic and proteomic analyses, we identified differential expression of genes and proteins involved in pathways that directly or indirectly regulate glycolysis in the CIA rats. Notably, we discovered novel differentially expressed enzymes implicated in the glycolysis pathway, such as hexokinase and fructose-bisphosphate aldolase, within the CIA rat model, which may serve as new markers for the diagnosis of RA or provide new perspectives to treat RA or RA-related glucose metabolism disorder.